Factors influencing adoption of cover crops for weed management in Machakos and Makueni counties of Kenya - Mwangi, H.W.; Kihurani, A.W.; Wesonga, J.M.; Ariga, E.S.; Kanampiu, F.K. (Elsevier, 2015)
Despite the many advantages of growing cover crops most farmers have not adopted them in their cropping systems. The objective of this study was to examine adoption and sociological factors associated with adoption of cover crops in Kalama (Machakos county) and Kee (Makueni county), Kenya. A semi-structured questionnaire was administered to 80 randomly selected participants to obtain sociological information including gender, age category, education levels, and adoption of cover crops. Two binary logistic regression models were used to determine the factors affecting cover crops adoption by respondents. Results showed that 80% of the respondents had adopted cover crop technologies at Kalama compared to 57.5% at Kee. Results indicated that gender had a significant (P < 0.05) effect on adoption. Men were less likely to adopt. Age category had mixed effects on cover crop adoption. At Kalama age category had a significant (P < 0.05) effect on cover crops adoption however age effect was not significant at Kee. Education indicated mixed effects on cover crop adoption suggesting other factors not covered in the study were at play. Views from farmers with experience in growing cover crops revealed that, knowledge and skills, demonstration of gains and related cost had a significant (P < 0.05) effect on cover crop adoption. Majority of farmers, adopters or non-adopters used seeds from market. Non-adopters in Kee (37.5%) used relief seed suggesting other factors were required to give the threshold required to influence adoption. This implies research is needed to identify factors with likelihood to reach threshold for adoption under different farming systems. The study recommends capacity building to develop cover crop knowledge and skills, demonstrate gains and related costs to improve men and women’s likelihood to adopt. In addition, the study recommends research to shed light on other factors likely to influence adoption.